2015
DOI: 10.1039/c4cp05546b
|View full text |Cite
|
Sign up to set email alerts
|

Excited state evolution of DNA stacked adenines resolved at the CASPT2//CASSCF/Amber level: from the bright to the excimer state and back

Abstract: Deactivation routes of bright ππ* (La) and excimer charge transfer (CT) states have been mapped for two stacked quantum mechanical (CASPT2//CASSCF) adenines inside a solvated DNA double strand decamer (poly(dA)·poly(dT)) described at the molecular mechanics level. Calculations show that one carbon (C2) puckering is a common relaxation coordinate for both the La and CT paths. By mapping the lowest crossing regions between La and CT states, together with the paths connecting the two states, we conclude that at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 91 publications
3
58
2
Order By: Relevance
“…Adenine and uracil are treated quantum mechanically (QM), and the rest of the system is treated with molecular mechanics (MM) using ONIOM and the AMBER force field. This hybrid approach is similar to those used in previous studies of nucleobase dinucleotides in solution or dimers embedded in oligomers . The potential energy study follows the CASPT2//CASSCF approach, which is well suited for excited states, for which the optimizations are carried out with CASSCF as the QM method, and the final energy is obtained with CASPT2.…”
Section: Resultsmentioning
confidence: 99%
“…Adenine and uracil are treated quantum mechanically (QM), and the rest of the system is treated with molecular mechanics (MM) using ONIOM and the AMBER force field. This hybrid approach is similar to those used in previous studies of nucleobase dinucleotides in solution or dimers embedded in oligomers . The potential energy study follows the CASPT2//CASSCF approach, which is well suited for excited states, for which the optimizations are carried out with CASSCF as the QM method, and the final energy is obtained with CASPT2.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the dI(20)‐DNA binary self‐assembly showed a broad emission band (400–700 nm) on excitation at 360 nm. The broad absorption and emission bands are consistent with emission from CT excited states of the nucleobases in double‐stranded DNA . Similarly, Banyasz et al.…”
Section: Resultsmentioning
confidence: 99%
“…Electron transfer is reasonable in heterodimers where one base is a better electron donor or acceptor, but it is less obvious that (partial) electron transfer can occur in a homo‐dimer like AA. Nevertheless, AA stacks have been intensively studied computationally, revealing excited dimer states with CT character …”
Section: Discussionmentioning
confidence: 99%
“…proposed that neutral excimers are responsible for the higher energy fluorescence on the subnanosecond timescale in (dA) n oligomers, while CT excimers give rise to the lower energy fluorescence seen beyond 1 ns. Conti et al . concluded that a CT excimer in an AA stack can deactivate via the same nuclear motions responsible for deactivation of the L a excited state associated with a single adenine.…”
Section: Discussionmentioning
confidence: 99%